Intimate partner violence and maternal educational practice - Josianne Maria Mattos da Silva; Marília de Carvalho Lima; Ana Bernarda Ludermir
ABSTRACT OBJECTIVE The objective of this study is to analyze the association between intimate partner violence against women and maternal educational practice directed to children at the beginning of formal education. METHODS This is a cross-sectional study, carried out between 2013 and 2014, with 631 mother/child pairs, registered in the Family Health Strategy of the Health District II of the city of Recife, State of Pernambuco, Brazil. It integrates a prospective cohort study designed to investigate the consequences of exposure to intimate partner violence in relation to the child who was born between 2005 and 2006. The maternal educational practice has been assessed by the Parent-Child Conflict Tactics Scale and the intimate partner violence by a questionnaire adapted from the Multi-Country Study on Women's Health and Domestic Violence of the World Health Organization. Intimate partner violence referred to the last 12 months and was defined by specific acts of psychological, physical, and sexual violence inflicted to women by the partner. The crude and adjusted prevalence ratios were estimated for the association studied, using log-binomial regression. RESULTS The prevalence of intimate partner violence was 24.4%, and violent maternal educational practice was 93.8%. The use of non-violent discipline was mentioned by 97.6% of the women, coexisting with violent strategies of discipline. Children whose mothers reported intimate partner violence presented a higher chance of suffering psychological aggression (PR = 2.2; 95%CI 1.0-4.7). CONCLUSIONS The violence suffered by the mother interferes in the parental education. The findings show high prevalence of violent maternal educational practice, pointing to the need for interventions that minimize the damage of violence in women and children.